Pengaruh Pertumbuhan Ekonomi, Pengangguran, Investasi, dan Dana Alokasi Umum (DAU) terhadap Ketimpangan WIilayah di Provinsi Banten Tahun 2005-2021 - Fachri Hafidy Syahputra Sinik; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2023)
Regional inequality in Banten Province is the highest among all provinces located on Java Island. Since 2005-2021, it has experienced an increasing trend and is still classified as high. This study aims to analyze the effect of economic growth, unemployment, investment, and general allocation funds on regional inequality in Banten Province in 2005-2021. This research uses a quantitative approach with data sourced from the Badan Pusat Statistik of Banten Province. The method used is multiple linear regression with time series data. The research results show that economic growth has a negative effect on regional inequality. Unemployment has a positive effect on regional inequality. Investment has a negative effect on regional inequality. The general allocation fund has no effect on regional inequality. Suggestions that are expected to reduce regional inequality in Banten Province are creating sustainable economic growth, reducing the unemployment rate, and increasing investment.